The Effects of Propolis Extract Administration on HIV Patients Receiving ARV - Erwin Astha Triyono; Sarah Firdausa; Heru Prasetyo; Joni Susanto; James Hutagalung; Lilis Masyfufah; Budiono Budiono; Ivan Hoesada (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Human Immunodeficiency Virus (HIV) is an infectious disease that targets the human immune system by attacking cluster of differentiation (CD)4 cells. The use of propolis in HIV patients is expected to be safe and beneficial in terms of increasing endurance and immunity by its role in increasing CD4 level. This study aimed to analyze the influence of propolis supplementation in increasing the CD4 level in anti-retroviral (ARV)-treated HIV patients.METHODS: Double-blind randomized controlled clinical trial was conducted in 50 HIV patients who took regular ARV therapy. The subjects were divided into two groups, one group was treated with ARV and propolis, while another one was given ARV and placebo. The CD4 cell count was measured during pre-treatment, in the 3rd month, in the 6th month after treatment. The level of hemoglobin, leukocyte, and platelets were also measured. The SF-12 questionnaire was used to evaluate quality of life of the subject.RESULTS: Out of 50 subjects, 43 subjects completed the study, which were 19 subjects from the propolis group and 24 subjects from the placebo group. After 3-month of treatment, there was a statistically significant difference in the increase of CD 44 level in propolis group, while the increment was not significant in the placebo group. After 6-month treatment, the increase of CD4 level was occurred in both groups, propolis and placebo, however the increment was not statistically significant. The levels of hemoglobin, leukocyte, and platelets were not altered by the treatment and remained normal throughout the study. The quality of life was improved during the study; however, it was also not statistically significant. Mild adverse events occurred in 3 subjects which were relieved after the treatment stopped.CONCLUSION: Based on the result of this study, the administration of propolis on HIV patients receiving ARV bring significant difference in the increase of CD4 in propolis group from baseline to 3 month after the treatment. While in placebo group, this increment was not significant. At the end of study, CD4 count continued to rise up, however the increase was not statistically significant. There are no hemoglobin, leukocyte, platelets, and quality of life abnormalities. Therefore, it is necesary to do further research with a spesific CD4 count. However, it may be beneficial in relieving the clinical symptoms and quality of life of patient living with HIV.KEYWORDS: CD4, ARV, HIV, propolis